Physical Training in ICD Patients: Safety, Clinical Results, and Quality of Life Improvements - Strzępek, Aleksandra; Łyżwa, Julia; Chmurska, Agnieszka; Janaszek, Agnieszka; Smerdzyński, Mateusz; Majchrzyk, Aleksandra; Frączek, Karolina; Kałwa, Natalia; Kałuża, Kinga; Pater, Michał (Journal of Education, Health and Sport, 2026)
Background: Implantable cardioverter-defibrillators (ICDs) represent the most effective therapy for the prevention of sudden cardiac death in patients at high risk of malignant ventricular arrhythmias. Despite their proven survival benefit, many patients limit physical activity due to fear of arrhythmia or device shocks, which may negatively affect functional capacity and quality of life. Aim: The aim of this study was to summarize current evidence on the safety of exercise training in patients with ICDs and to analyze the impact of device therapy on patients’ physical activity levels. Material and Methods: A PRISMA-compliant literature review was conducted via PubMed, focusing on studies published between 2021–2026. Keywords included "ICD," "exercise training," "safety," "shock," and "quality of life." Specific case reports were included to provide insights into unique clinical interactions and the impact of exogenous substances. Results: Available evidence, including randomized controlled trials and meta-analyses, indicates that moderate aerobic exercise and structured cardiac rehabilitation programs are safe in ICD recipients and do not significantly increase the risk of ventricular arrhythmias or ICD shocks. The incidence of shocks during exercise is very low. However, experiencing ICD shocks is associated with a significant decline in daily physical activity and increased anxiety, whereas antitachycardia pacing (ATP) does not produce similar behavioral effects. Regular exercise improves cardiorespiratory fitness (VO₂peak), autonomic modulation, and quality of life. Conclusions: Current evidence supports appropriately prescribed and supervised exercise training as a safe and beneficial component of comprehensive care in patients with ICDs. Current evidence suggests that sedentary recommendations are often unjustified, while individualized risk assessment and optimal device programming remain essential.